Endorsements from Republican politicians can increase confidence in U.S. elections. (10th January 2023) - Clayton, Katherine; Willer, Robb
Since the 2020 U.S. presidential election, perceptions of the validity of the outcome and broader trust in the American electoral process have reached historically low levels among Republicans. While this trend has potentially harmful consequences for democratic stability, there is little research on how beliefs that an election was fair—and trust in the electoral process more generally—can be restored. In a preregistered survey experiment ( n = 2101), we find that viewing real messages from Republican politicians defending the legitimacy of the 2020 election increased faith in the election's outcome and in the broader electoral process among Republican voters, compared to either a neutral control condition or to comparable messages from Democratic politicians. These effects are statistically mediated by shifts in voters' perceptions of elite Republican opinion about the 2020 election, highlighting a potentially useful intervention for efforts to restore faith in elections going forward. Notably, exposure to messages from Republican politicians affirming the election's legitimacy did not significantly decrease support for the Republican Party, suggesting that Republican politicians who endorse the 2020 election results might not face backlash from voters.